Stereological Study of Changes of GABA-Immunoreactive Neurons in Spinal Dorsal Horn of SNI Rats. (18th June 2021) - Liu, Hong; Li, Weidong; Xu, Binbing; Jiang, Jiduan; Zhang, Yuanyuan; Yang, Fan
Abstract : Objective . To observe the changes in the mechanical withdrawal threshold (MWT) and the proportion of GABA-immunoreactive neurons in spinal dorsal horn (SDH) of the spared nerve injury (SNI) rat model. Methods . Thirty-six healthy male SD rats were randomly divided into a sham-operated group (group D, n = 18 ) and an SNI group (group S, n = 18 ). The left sciatic nerve trunk and three branches were exposed, two of which, known as tibial and the peroneal nerve, were ligated and cut off. The sural nerve was preserved to build the SNI model in group S. The left sciatic nerve trunk and three branches were only exposed in group D. MWT tests were performed on the medial and lateral sides of the rats' left hindpaw 1 day before surgery and at 7 th, 14 th, and 28 th day after surgery. Results . In group S, compared with the baseline measured 1 day before surgery, MWT on the medial and lateral sides of the rats' left hindpaw decreased significantly on the 7 th, 14 th, and 28 th days after surgery (P < 0.05 ), while in group D, there was no statistically significant difference (P > 0.05 ). Compared with right SDH, there were not statistically significant reductions in the proportions of GABAergic neurons of left SDH on 7 th and 28 th day after SNI (P > 0.05 ); however, the proportion of GABAergic neurons in left SDH significantly decreased, compared with that in right side on 14 th day after SNI (P < 0.05 ). On the same way, the proportions of GABAergic neurons on 7 th, 14 th, and 28 th day after surgery were not statistically different (P > 0.05 ) in group D. Conclusion . The SNI model could reduce the proportion of GABA-immunoreactive neurons in the rat's spinal dorsal horn on the nerve-injured side, and this change was lasting, which might be related to the transformation of the GABA-immunoreactive neurons.